HUBUNGAN ANTARA PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DENGAN EFEKTIVITAS PENGENDALIAN BIAYA - Andi Indra Martini (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
The objective of this research is to know and evaluate the concept of responsibility accounting applied as a tools of management at a service company in reaching effectiveness financial control and to analyze whether there are a relationship between applying responsibility accounting with the financial control effectiveness. Research method the used is quantitative method with the survey technique, that is research method taking sample from one population and use questioner as a tools of data collecting, then processed, analyzed and also also compared to existing theory, while data examination used data examination and device of hypothesis examination. From result of research which writer have execute in five hotel in Tasikmalaya, the company have applied responsibility accountancy good enough, this matter can know pursuant to conditions which must be fulfilled. The final examination obtained from two center of responsibility in five hotel that become responder are that there are positive relationship between applying adequate responsibility accounting with the financial control effectiveness, with correlation level 60 % where examination conducted use the Correlation Coefficient Analysis rank Kendall.